An electricity triangle for energy transition: Application to Italy. (1st November 2020) - Bompard, E.; Botterud, A.; Corgnati, S.; Huang, T.; Jafari, M.; Leone, P.; Mauro, S.; Montesano, G.; Papa, C.; Profumo, F.
Highlights: Electricity and electrification is a viable solution for the energy transition. Electricity triangle assures a consistent framework for the energy transition. Multifaceted benefits: energetic, environmental and socio-economic. Conceptualization of a set of metrics for impact assessment. A real case study (Italy) considering its evolution up to 2050. Abstract: Greenhouse gases along with pollution generated by the present energy paradigm widely based on fossil fuels are providing large impacts in terms of climate change and the health of human and biological systems at large. A shift in the energy paradigm, from fossil fuels to renewable energy, is urgently needed for nature and society. This is what we refer to as the energy transition. An old commodity – electricity – can play a new key role in the energy transition. That can happen through what we call the electricity triangle involving electricity generation from Renewable Energy Sources, exploitation of electricity as the main energy vector, and electrification of the final energy uses in all sectors. The possible deployment of the electricity triangle must be carefully assessed in all its possible implications, from technological, economic, societal and environmental perspectives. In this paper, we conceptualize the electricity triangle as a viable approach to the energy transition, and we propose a set of holistic metrics to assess its possible impacts. We apply the electricity triangle framework to the case of Italy based on sectorial studies on RES generation and electrification in building, industry and transport sectors. Our results indicate that Italy in 2050 has the potential to achieve 85.6% penetration of RES in its electricity supply, while 41%, 53% and 42% of the energy consumptions in transport, residential, and industry sectors will be electrified. Ultimately, this would lead to a 68% reduction in CO2 emissions compared to current levels.